PowToon as a Teaching Tool for Junior High Writing Skills: PowToon sebagai Alat Bantu Pengajaran untuk Keterampilan Menulis di Sekolah Menengah Pertama - Alifina, Vienna Rahmi; Novita, Dian (Indonesian Journal of Education Methods Development, 2025)
General Background: Writing is a crucial communication skill that students must develop, yet many struggle with it. Integrating technology in education has been shown to enhance learning engagement and effectiveness. Specific Background: Traditional methods of teaching writing often fail to capture students' interest, leading to poor writing performance. PowToon, a multimedia-based tool, has gained attention as a potential solution for improving writing skills. Knowledge Gap: While previous studies have explored the effects of PowToon in online learning, research focusing on its impact on junior high school students' writing abilities through quantitative analysis remains limited. Aims: This study examines the effect of PowToon on students' descriptive text writing skills using a pre-experimental design with a pre-test and post-test approach. Results: The paired sample t-test results (t = 5.910, p < 0.05) indicate a statistically significant improvement in students' writing performance after using PowToon, confirming the effectiveness of this tool in enhancing writing skills. Novelty: Unlike previous studies that used qualitative approaches, this research employs a quantitative method to assess PowToon's impact, providing measurable evidence of its benefits for junior high school students. Implications: The findings suggest that integrating PowToon into writing instruction can enhance students' engagement and learning outcomes, supporting its adoption in language education. Highlights: Technology-Enhanced Learning: PowToon significantly improves students' writing skills by providing engaging, multimedia-based learning experiences. Quantitative Evidence: The study's statistical analysis confirms a measurable improvement in students' descriptive writing abilities after using PowToon. Pedagogical Implications: Integrating PowToon into writing instruction can enhance student motivation and learning outcomes in language education. Keywords: Powtoon, Writing, Teaching Media, Descriptive Text, Junior High School